Different cephalic development among rabbit types - Parés-Casanova, Pere M. (2018)
The word “allometry” refers to the relative growth of a biological structure to other(s) or to the entire body, and encompasses conformational changes due to size change. When growth is the same among studied traits, it is known as “isometry”. In order to study this phenomenon in domestic rabbit, a sample of 71 fresh post-weaned rabbit corpses of different age was collected, and skulls were obtained and defleshed. Of this sample, 59 corpses were from companion type (“toys” and “beliers”) and 12 from meat type (Californian/New Zealand) rabbits. From each skull it was obtained a digital picture, on its lateral aspect, and 12 anatomical landmarks were situated on it and analysed by means of geometric morphometric methods. Meat rabbits presented a clear isometric growth, although they were still growing (e. g. have not reached to final growth stage) while companion rabbits presented a clear allometric growth (e. g. adults have not reached a final growth). So, it is illustrated a case of gerontomorphy for meat rabbits —e. g. an early development of skull traits— and a case of pedomorphy for companion rabbits —e. g. a delayed growth in skull traits in order to mantain typical juvenile traits as a short and plain face, and a comparatively big cranium—. In other words, for the former group, a precocious development was detected, while for the latter, it was detected a retention of juvenile traits, being for both types cases of developmental heterochronies.